Mentoring Practices of Principals for Teachers’ Retention in Public Secondary Schools in Anambra State, Nigeria - Anachuna , Obinna Nonso; Obi, Emenike (European Scientific Journal, ESJ, 2021)
The seeming teacher turnover in secondary schools in Nigeria necessitated this study on mentoring practices of principals for teachers’ retention in public secondary schools in Anambra State. The study adopted the descriptive survey research design. One research question guided the study. The population of the study comprised 256 principals and the entire population was used for the study. Researchers’ developed questionnaire was the instrument used for data collection. The instrument was validated by three experts, two in Educational measurement and evaluation, Department of Educational Foundation and the other in Educational planning and management, Educational Management and Policy, all in the Faculty of Education Nnamdi Azikiwe University, Awka. The Cronbach’s alpha method was used to determine the internal consistency of the items which yielded a reliability coefficient of 0.75. The researchers with the help of ten research assistants distributed and successfully collected 256 copies of the questionnaire administered. The research question was answered using the arithmetic mean. It was found among others that principals in public secondary schools in Anambra state use formal and informal mentoring to a very low extent for teachers’ retention. Based on the findings of the study, it was recommended among others that government should provide adequate resources necessary for effective mentoring programme in secondary schools in Anambra State.